Milk Fermented by Lactic Acid Bacteria Enhances the Absorption of Dietary Sphingomyelin in Rats. Issue 5 (29th March 2017) - Morifuji, Masashi; Kitade, Masami; Oba, Chisato; Fukasawa, Tomoyuki; Kawahata, Keiko; Yamaji, Taketo; Manabe, Yuki; Sugawara, Tatsuya
Abstract : Abstract: Supplementation with sphingomyelin has been reported to prevent disease and maintain good health. However, intact sphingomyelin and ceramides are poorly absorbed compared with glycerolipids. Therefore, if the bioavailability of dietary sphingomyelin can be increased, supplementation would be more effective at lower doses. The aim of this study in rats was to evaluate the effect of fermented milk on the bioavailability of dietary sphingomyelin in rats. After the rats had fasted for 15 h, test solutions were administrated orally. Blood samples were collected from the tail vein before and 90, 180, 270, and 360 min after administration. Compared with sphingomyelin/milk phospholipids concentrate (MPL) alone, co‐ingestion of sphingomyelin/MPL with fermented milk caused an approximate twofold significant increase in serum ceramides containing d 16:1 sphingosine with 16:0, 22:0, 23:0 and 24:0 fatty acids, which was derived from the ingested sphingomyelin. While nonfat milk also increased the serum levels of these ceramides, fermented milk was more effective. Co‐ingestion of the upper layer of fermented milk or exopolysaccharide concentrate prepared from fermented milk significantly increased serum ceramide levels. X‐ray diffraction analysis also showed addition of fermented milk or EPS concentrate to sphingomyelin eliminated the characteristic peak of sphingomyelin. This study demonstrated for the first time that co‐ingestion of dietary sphingomyelin and fermented milk, compared with ingestion of dietary sphingomyelin alone, caused a significant increase in the absorption of sphingomyelin. Our results indicate exopolysaccharides in fermented milk may contribute to inhibition of sphingomyelin crystallization, resulting in enhanced absorption of dietary sphingomyelin in rats.